2006
DOI: 10.2337/dc06-0650
|View full text |Cite
|
Sign up to set email alerts
|

Early Involvement of the Spinal Cord in Diabetic Peripheral Neuropathy

Abstract: Spinal cord involvement occurs early in DPN. There is also a significant relation between reduction in SCAI and neurophysiological assessments of DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
1
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(97 citation statements)
references
References 37 publications
4
85
1
7
Order By: Relevance
“…Images are presented according to neurologic convention, with right hemisphere structures shown on the right. However, evidence is now emerging that the impact of this disorder may be more generalized than previously thought, involving the spinal cord and thalamus (8,10,35). It seems logical therefore to investigate whether other areas of the brain may also be affected by the neuropathic process.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Images are presented according to neurologic convention, with right hemisphere structures shown on the right. However, evidence is now emerging that the impact of this disorder may be more generalized than previously thought, involving the spinal cord and thalamus (8,10,35). It seems logical therefore to investigate whether other areas of the brain may also be affected by the neuropathic process.…”
Section: Discussionmentioning
confidence: 97%
“…However, the relevance to the pathogenesis of neuropathy depends on whether there are changes in the brain of patients with early (subclinical) neuropathy. We have previously demonstrated that spinal cord atrophy appears to occur early in the neuropathic process, which, if also observed in the brain, would suggest that extensive and perhaps even irreversible damage may have occurred (8). Indeed, with this in mind, it is not surprising that, so far, the variety of therapeutic options attempted in subjects with DPN have been unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important approach is the use of combination treatments; a recent trial showed that use of morphine and gabapentin together is superior to either alone in individuals with neuropathic pain, with gabapentin similar to placebo, although combination treatment was associated with an increased frequency of side effects, including constipation, dry mouth, and sedation (42). For many patients, Tesfaye suggested, "the remedy is worse than the disease," so that we need to better understand the pathogenesis of pain in neuropathy and distinguish peripheral from central pain, with a potentially important contributory factor being spinal cord abnormality (43), which his group has found to occur early in the development of diabetic neuropathy (44). Magnetic resonance imagining sprectroscopy shows abnormality of the thalamus, which acts as a gateway for pain, to occur in individuals with painful neuropathy.…”
Section: Diabetic Neuropathymentioning
confidence: 99%
“…27 Furthermore, a larger prospective study reported significantly lower mean spinal cord area in clinically asymptomatic diabetic patients with subclinical neuropathy compared to those without neurophysiological abnormalities. 28 Marked abnormalities in somatosensory-evoked potentials within the spinal cord may be present in patients with severe painful diabetic neuropathy and nearly normal peripheral sensory nerve conduction study. 29 These findings suggest that spinal cord involvement may be considered as an early manifestation in the course of neuropathy.…”
mentioning
confidence: 99%